2020
DOI: 10.1021/jacs.9b13157
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of Homochiral Benzene-1,3,5-tricarboxamide Helical Assemblies and Catalysts upon Addition of an Achiral Monomer

Abstract: Chirality amplification refers to the ability of a small chiral bias to fully control the main chain helicity of polymers and assemblies. Further implementation of functional chirally-amplified helices as switchable asymmetric catalysts, chiral sensors and circularly-polarized light emitters will require a greater control of the energetics governing these chirality amplification effects. In this work, we report on the counterintuitive ability of an achiral molecule to suppress conformational defects in supramo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
100
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(116 citation statements)
references
References 99 publications
11
100
0
Order By: Relevance
“…Those concerning BTA Leu , BTA Nle and BTA Phe as sergeants are examined into more details in the following as they are representative of the trend exhibited by the other sergeants (vide infra). For BTA Leu , the CD intensity increases gradually until the fraction of sergeant is ≈40 % and then reaches a plateau corresponding to a g value of 7.7×10 −4 (Figure 1 b) close to the one recorded for the best S&S‐type mixtures (g max ≈7.0×10 −4 ) [8e] . This value is considered as the maximal value that can be reached for this type of helical assemblies and will be referred to as the homochiral state in the following discussion.…”
Section: Resultssupporting
confidence: 64%
See 2 more Smart Citations
“…Those concerning BTA Leu , BTA Nle and BTA Phe as sergeants are examined into more details in the following as they are representative of the trend exhibited by the other sergeants (vide infra). For BTA Leu , the CD intensity increases gradually until the fraction of sergeant is ≈40 % and then reaches a plateau corresponding to a g value of 7.7×10 −4 (Figure 1 b) close to the one recorded for the best S&S‐type mixtures (g max ≈7.0×10 −4 ) [8e] . This value is considered as the maximal value that can be reached for this type of helical assemblies and will be referred to as the homochiral state in the following discussion.…”
Section: Resultssupporting
confidence: 64%
“…This signal is absent from solutions containing only the soldier (because it is achiral) or containing only the sergeant (because it has no absorption band in this region). Such an induced CD signal (ICD) is indicative of the extent of chirality induction of the soldier by the sergeant [8e] . The corresponding CD intensities, under the form of the Kuhn anisotropy factor (g 295 , see the caption of Figure 1), offer the possibility to compare the degree of helicity of the different co‐assemblies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is still difficult to predict self‐assembled supramolecular chirality based on a known peptide sequence that contains more than one chiral center [15–17] . Recently, some intriguing investigations into the chiral amplification phenomenon have been reported [36–38] . For example, Xu and co‐workers investigated the self‐assembly chirality of three pairs of short tetrapeptide enantiomers and found that the handedness of the supramolecular nanofibrils was determined by the chirality of the hydrophilic Lys head at the C terminus, whereas the morphological handedness could not be changed by altering the molecular chirality of hydrophobic Ile residues [16] …”
Section: Introductionmentioning
confidence: 99%
“…[505][506][507][508][509] Conformational defects have further been investigated in the context of chirality amplification in helical 1D supramolecular polymers. 510 Amplification of chirality is generally referred to as the ability of a small chiral bias to fully control or dictate the helicity of polymers and assemblies, 511 and was recently used to prepare functional helical nanostructures as asymmetric catalysts, 512 or chiral stationary phases. 513 Giuseppone and coworkers have used supramolecular polymers in the gel-state to combine the electronic properties of organic materials exhibiting metallic behavior, with the mechanical properties of soft self-assembled systems.…”
Section: Defects In Supramolecular Polymersmentioning
confidence: 99%